Interleukin-6 and insulin resistance in obese adolescents - Raynald Takumansang; Sarah M. Warouw; Hesti Lestari (Paediatrica Indonesiana, 2013)
Background Obesity has become a rapidly growing epidemic worldwide, increasing the risk of morbidity and mortality in adolescents. Obesity is due to an expansion of adipose tissue mass, which is an important source of cytokines and contributes to an increase in pro-inflammatory cytokines, such as interleukin-6 (IL-6). Interleukin-6 is significantly increased in obesity and may lead to a state of insulin resistance.Objective To assess for a correlation between IL-6 levels and insulin resistance in obese adolescentsMethods We conducted a cross-sectional study from January to April 2012 in Manado, North Sulawesi. Subjects were either obese or normal body mass index (BMI) teens aged 13-18 years. Data collected were anthropometric status, BMI, and blood specimens for fasting plasma glucose levels, fasting insulin levels, and IL-6 levels. Insulin resistance was expressed as homeostatic model assessment of insulin resistance (HOMA-IR) level >2.77. Data was analyzed by Pearson’s correlation and linear regression tests to assess for a possible correlation between IL-6 levels and insulin resistance.Results The mean BMI in the obese group was 31.21 (SD 3.61) kg/m2 while the mean BMI in the normal group was 19.52 (SD 2.38) kg/m2. There was no significant association between IL-6 and the occurrence of insulin resistance (P=0.309). The log regression coefficient value of IL-6 was negative (b = -0.329).Conclusion There is no correlation between IL-6 levels and incidence of insulin resistance in obese adolescents.